DEVELOPMENT OF SUSTAINABLE ULTRA-HIGH PERFORMANCE CONCRETE USING HIGH VOLUME FLY ASH AND ULTRAFINE CALCIUM CARBONATE - MOHD AZMEE, NORZAIREEN (2019)
Concrete technology advancement and expanding interest for high-quality construction materials have prompted the development of Ultra-High Performance Concrete (UHPC)